A novel tissue culture method to produce professional antigen-presenting cells from rainbow trout in vitro - Nguyen T. K. Vo, PhD; Lital Sever, PhD; Brian Dixon, PhD; Niels C. Bols, PhD (Comparative Immunology Reports)
In this study, we describe a tissue culture method to identify and produce large quantities of professional antigen presenting cells (pAPCs) including dendritic cells (DCs) using fin explant cultures from rainbow trout. After several months of in vitro incubation with a routine schedule of selective cell enrichment and specifically formulated medium nutrient feeding, flasks of fin explant cultures produced a heterogenous population of cells whose morphologies resembled those of monocytes, macrophages, melanomacrophages, and DCs, with DCs being present in a large quantity. These cells were collectively referred to as fin leukocyte-like cells (fin-LLCs). The RT-PCR result showed that the fin-LLCs expressed abundant transcript levels of four markers of pAPCs (Major Histocompatibility (MH) IIα, MH IIβ, S25–7, INXV), three transcript markers of DCs (CD83, CD205, CD209), one transcript marker for macrophages (CSF1R), and one transcript marker for pro-inflammatory responses (IL-1β). Using affinity-purified anti-trout MH IIα and MH IIβ primary antibodies that were generated in house, abundant levels of MH IIα and MH IIβ polypeptides were detected in fin-LLCs by Western blotting. Immunocytochemistry in combination with confocal microscopy showed that DC-like cells had more cell-surface MH II proteins than macrophage-like cells. These results suggest the fin-LLCs had characteristics and markers of pAPCs. As fin clipping does not threaten the survival of fish and fins are natural regenerative appendages, our method allows the large production of autologous fish APCs in vitro, which can be used for many other research purposes in the future.